2023
DOI: 10.1136/bmjgh-2023-012203
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Global Health Security Index as a predictor of COVID-19 excess mortality standardised for under-reporting and age structure

Abstract: BackgroundPrevious studies have observed that countries with the strongest levels of pandemic preparedness capacities experience the greatest levels of COVID-19 burden. However, these analyses have been limited by cross-country differentials in surveillance system quality and demographics. Here, we address limitations of previous comparisons by exploring country-level relationships between pandemic preparedness measures and comparative mortality ratios (CMRs), a form of indirect age standardisation, of excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 93 publications
1
8
0
1
Order By: Relevance
“…Por el contrario, estados como Aguascalientes, Quintana Roo, Guerrero y Chiapas destacaron por su eficacia. Lo anterior puede parecer inesperado, ya que comúnmente se anticipa un rendimiento superior en zonas con un índice Según Ledesma et al, 27 una relación coherente con las expectativas emerge al ajustar por subnotificación y considerar la distribución por edad. Además, Bollyky y Hulland 28 señalaron previamente que factores como la confianza en las instituciones gubernamentales, la confianza entre ciudadanos y un menor nivel de corrupción gubernamental se correlacionan positivamente con tasas de infección estandarizadas más bajas, con descensos más pronunciados en la movilidad y con una amplia cobertura de la vacunación contra COVID-19, especialmente en países con ingresos medios y altos donde las vacunas son ampliamente accesibles.…”
Section: Discussionunclassified
“…Por el contrario, estados como Aguascalientes, Quintana Roo, Guerrero y Chiapas destacaron por su eficacia. Lo anterior puede parecer inesperado, ya que comúnmente se anticipa un rendimiento superior en zonas con un índice Según Ledesma et al, 27 una relación coherente con las expectativas emerge al ajustar por subnotificación y considerar la distribución por edad. Además, Bollyky y Hulland 28 señalaron previamente que factores como la confianza en las instituciones gubernamentales, la confianza entre ciudadanos y un menor nivel de corrupción gubernamental se correlacionan positivamente con tasas de infección estandarizadas más bajas, con descensos más pronunciados en la movilidad y con una amplia cobertura de la vacunación contra COVID-19, especialmente en países con ingresos medios y altos donde las vacunas son ampliamente accesibles.…”
Section: Discussionunclassified
“…While we included 2020 for completeness in year-on-year graphs, 2020 was excluded from group and time-trend analyses, to prevent any skew from the heavily suppressive effect of Covid-19 pandemic control measures on winter illness mortality rates (NZ experienced negative total excess mortality in the 2020 and 2021 years (Knutson et al 2023 ; Ledesma et al 2023 )). We did not exclude the years affected by poliomyelitis epidemic control measures in the summers of 1924–1925, 1936–1937 or 1947–1948 (Ross 1994 ), as there was no visible effect of these measures on total mortality or EWMs for those years, compared to years either side.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that the paradoxical outcomes may have been the result of an oversimplified analysis that, among other factors, did not appropriately adjust for population age and misclassification of a COVID-19 death (Markovic et al, 2022). For example, when adjusting for these factors Ledesma et al (2023) found an association between greater preparedness and lower excess mortality. While countries can be held accountable to one another to build and maintain health security capacities, this is not the case for effective political leadership and wider societal factors that influence whether or not health security capacities are used effectively (Stoto, Nelson & Kraemer, 2023).…”
Section: Box 314 Health Security Indices and Covid-19 Outcomesmentioning
confidence: 99%